Notes on the Morphology, Anatomy, Palynology, and Karyology of Onobrychis argaea (Fabaceae), Endemic to Turkey - Atasagun, Bayram; Aksoy, Ahmet; Marti̇n Esra (Phytotaxa, 2024)
Onobrychis argaea belonging to the Fabaceae family, is an endangered plant species endemic to Turkey, distributed only in Kayseri Erciyes Mountain. This study represents the first comprehensive investigation into the morphology, anatomy, pollen and seed micromorphology, and chromosome characteristics of O. argaea. The previous description of the species has been expanded and modified. The pith of the root is covered with xylem tissue. In the stem cross-section, the protective tissue is periderm in the woody part and epiderm in the herbaceous part. The leaflets are amphistomatic and equifacial. The pollen grains are radially symmetric, isopolar, tricolpate, with prolate shape and reticulate-microreticulate ornamentation. The seeds are reniform, yellowish-brown, suboblate, and exhibit rugulate surface ornamentation. The number of somatic chromosomes in O. argaea is 2n = 14. The karyotype formula of this species consists of seven median chromosomes.